Enhancing community consensus in Oman tourism: A communication approach - Tripathi, Sangeeta (Jurnal Kajian Komunikasi, 2025)
Background: As the world pays increasing attention to innovations in the tourism sector, this study will examine how local communities respond to such innovations, particularly in Oman, which is diversifying its economy through tourism. This study highlights several factors influencing stakeholders’ acceptance of innovative tourism, including local communities, businesses, and tourism students. Purpose: This study aimed to identify the determinants of whether tourism enterprises adopt innovative practices and effective communication strategies to diffuse information and create awareness regarding creative tourism. Methods: The current study employed a quantitative methodological approach based on data gathered from 533 respondents representing a cross-section of tourism industry stakeholders. Results: The findings illustrate significant considerations regarding the acceptability of Oman’s new tourism development, with a great emphasis on communication strategies. Equally, the research outlines real implications for countries interested in developing innovative tourism by highlighting a pronounced active community approach. This study was conducted in specific geographic regions, which limits the generalizability of the findings. Therefore, future studies can be performed with a broader selection of locations and stakeholder perspectives to increase the validation of the Diffusion of Innovation model for tourism contexts. Conclusion: This study emphasizes the need for community participation in tourism innovation processes. A sense of ownership creates more enthusiasm and cohesion among local stakeholders and encourages them to accept new tourism practices socially. Implications: This research strengthens community dialogue regarding tourism. This study adds to the literature on the diffusion of innovation in the tourism industry by providing empirical evidence on the adoption of innovative tourism practices.